Two‐Photon Laser‐Written Photoalignment Layers for Patterning Liquid Crystalline Conjugated Polymer Orientation. (30th November 2020) - Shi, Yuping; Salter, Patrick S.; Li, Mo; Taylor, Robert A.; Elston, Steve J.; Morris, Stephen M.; Bradley, Donal D. C.
Abstract: Systematic tuning of chemical and physical structure allows fine control over desired electronic and optical properties, including those of conjugated polymer semiconductors. In the case of physical structure, orientation via liquid crystalline alignment allows access to fundamental optical anisotropies and the associated refractive index modification offers great potential for fabrication of photonic structures. In this paper, photoalignment is used to orient the liquid crystalline conjugated polymer poly(9, 9‐dioctylfluorene‐co‐benzothiadiazole) (F8BT), specifically involving two‐photon infrared laser writing of patterns in an azobenzene sulphonic dye (SD1). These patterns are transferred into the overlying film by thermotropic orientation in the nematic melt, then frozen in place by quenching to a room temperature nematic glass. Optimization of laser power and scan speed allows features with linewidths ≤ 1 µm. Photoluminescence (PL) peak anisotropy values reach PLII /PL⊥ = 13 for laser writing, compared with PLII /PL⊥ = 9 for polarized ultraviolet light emitting diode exposure of the same SD1 layer. These two approaches also result in different film microstructures; evidenced by characteristic changes in PL spectra. The anisotropic PL spectra provide information on emissive excited states that complements previous studies on non‐oriented F8BT and related copolymers, also suggesting two emissive states. Abstract : High resolution, sub‐micron patterning of liquid crystalline conjugated polymers (LCCP) is demonstrated using two‐photon laser writing, offering great flexibility for the construction of optical structures for a variety of applications. The image displays a college crest patterned by laser writing on a uniformly aligned photoalignment film on top of which the LCCP has been oriented as a nematic glass.